Principal Management in Optimizing Teacher Potential to Improve Learning Quality and School Branding at SD Negeri Karangdukuh, Klaten Regency - Amelia Nirha Khartikasari; Didi Supriadi; Rahmat Mulyono (JURNAL MANAJEMEN PENDIDIKAN, 2026)
This study aims to describe the principal’s management in optimizing teachers’ potential and school resources to improve the quality of learning and school branding at SD Negeri Karangdukuh. This research employed a qualitative descriptive approach, with data collected through interviews, observations, and documentation. The research subjects included the principal and teachers. Data analysis was conducted through the stages of data reduction, data display, and conclusion drawing. The findings indicate that the principal implements potential-based management through four main stages: planning, organizing, implementation, and evaluation. The principal is able to identify teachers’ potential and assign them according to their competencies, effectively manage school facilities and infrastructure, and foster a collaborative working culture. The impact of this management is reflected in the improvement of learning quality, the achievement of school accomplishments that had not previously been attained—at least at the sub-district level—and the increase in student enrollment. Therefore, potential-based principal management has been proven to significantly contribute to improving educational quality and strengthening the school’s image.